Investigation on applicability of time-averaged X-ray CT images in two-phase flow measurement. Issue 12 (2nd December 2019) - Nukaga, Jun; Katono, Kenichi; Sadaoka, Noriyuki; Yasuda, Kenichi; Aoki, Toru
ABSTRACT: Measuring the void fraction between fuel rods contributes to optimizing the geometrical design of fuel bundles for boiling water reactors (BWR). In this article, a method for reconstructing a three-dimensional void fraction distribution of two-phase flow by using an X-ray CT system is proposed. The performance was evaluated by both simulation and experiment. The simulation results suggested that the accuracy of the proposed method was within ±0.02, and from the experimental results, the void fraction in gas-liquid two-phase flows was successfully obtained with sufficient accuracy.